2015
DOI: 10.2527/jas.2014-8688
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nitrate addition and increased oil content as methane mitigation strategies for beef cattle fed two contrasting basal diets1

Abstract: The objectives of this study were to investigate the effects of (1) the addition of nitrate and (2) an increase in dietary oil on methane (CH4) and hydrogen (H2) emissions from 2 breeds (cross-bred Charolais and purebred Luing) of finishing beef cattle receiving 2 contrasting basal diets consisting (grams per kilogram DM) of 500:500 (Mixed) and 80:920 (Concentrate) forage to concentrate ratios. Within each basal diet there were 3 treatments: (i) control treatments (mixed-CTL and concentrate-CTL) contained rape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
55
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(72 citation statements)
references
References 23 publications
9
55
3
4
Order By: Relevance
“…reduced energy loss) from steers offered the Mixed diet (Troy et al, 2015); however no response was observed in the present study on FCR or RFI. The benefits in reduced energy loss as CH 4 observed by Troy et al (2015) may have been counterbalanced by sub-clinical effects of nitrate. In contrast, nitrate improved the FCR of steers offered the Concentrate diet, but with no aligned reduction in CH 4 (Troy et al, 2015).…”
contrasting
confidence: 91%
See 4 more Smart Citations
“…reduced energy loss) from steers offered the Mixed diet (Troy et al, 2015); however no response was observed in the present study on FCR or RFI. The benefits in reduced energy loss as CH 4 observed by Troy et al (2015) may have been counterbalanced by sub-clinical effects of nitrate. In contrast, nitrate improved the FCR of steers offered the Concentrate diet, but with no aligned reduction in CH 4 (Troy et al, 2015).…”
contrasting
confidence: 91%
“…In the present study, steers offered a higher proportion of concentrate in the diet expressed better feed efficiency (RFI) than those offered a mixed forage : concentrate diet. These steers were also shown to have lower levels of CH 4 production compared to steers offered higher quantities of forage (Troy et al, 2015).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations